Mapping Diversity in Social History - Ercole Sori (Fondazione Eni Enrico Mattei (FEEM), 2003)
The paper is an overview of diversity in history, starting as far back as the societies in classical Ancient Europe and traditional non-European societies, where differentiation was basically between the enslaved and free population and the out-of-caste in India. With the end of slavery the European feudal society adopted a functionalist tripartition based on priests, warriors and peasants. The analysis continues in pre-industrial Europe (1500-1800), where in many cities class struggle was represented by the conflicts between crafts and between cities, with some participation of the élites. In 17th century England only one class existed, and class struggle was the struggle inside one class. Other considerations on the stratification of pre-industrial society are related to classes inferred from empirical subjectivity, social hierarchy and horizontal and vertical solidarity. In industrial society, the paper discusses the Marxian, Weberian and Marshall models and the syncretism between status and class. The second part of the paper is devoted to diversity outside formal society with the definitions of the processes that generate the marginalization of people and social groups, while the third part of the paper concerns the urban milieu and social integration/differentiation. Considerations are made on urban topography (e.g. ghettos, miracle courts, etc.) and on the relationship between topographic position within the urban tissue and positioning in the social pyramid. Finally, the last part of the paper is an excursus on the historiographic assumptions and policies toward diversity and marginality.
Keywords: N30; 330; Diversity; Marginalization; Social history; Social integration; Social Differentiation